Anterolateral thigh free flap using modified turbocharging method: a case report - Ha, Yooseok; Kim, Donghyun; Kwon, Hyeokjae; Kim, Sunje; Song, Seung Han; Oh, Sang-Ha; Kim, Joo-hak; Yang, Ho Jik; Kyung, Hyunwoo (Frontiers in Surgery, 2024)
The free flap is a versatile option for reconstruction of soft tissue defects around the ankle. In patients with poor lower leg circulation, arterial insufficiency is one of the complications that can occur immediately after vessel anastomosis during free flap surgery. The authors were able to improve blood circulation in the flap by using modified turbocharging method in which another perforator was anastomosed to the distal end of the main pedicle.